Boswellia serrata extract shows cognitive benefits in a double-blind, randomized, placebo-controlled pilot clinical trial in individuals who suffered traumatic brain injury. (21st March 2022) - Meshkat, Shakila; Mahmoodi Baram, Somayeh; Rajaei, Shima; Mohammadian, Fatemeh; Kouhestani, Emad; Amirzargar, Nasibeh; Tafakhori, Abbas; Shafiee, Sajad; Meshkat, Melika; Balenci, Laurent; Kiss, Alex; Riazi, Ali; et al.
ABSTRACT: Background: Traumatic brain injury (TBI) is a major cause of death and disability. TBI can result in neuropsychiatric and cognitive problems as well as neurodegenerative pathologies that can appear right after or develop and persist years after injury. Method: We conducted a double-blind, randomized, placebo-controlled clinical trial on patients who suffered from TBI three months to three years ago. The patients were randomized to placebo (n = 34) or K-Vie™ group (n = 46) for a treatment period of 3 months. The main primary outcomes include cognitive assessment in the Rey Auditory Verbal Learning Test-Recognition Test (RAVLT), Wechsler adult intelligence Digit Symbol Substitution Test (DSST) and trail-making test part B (TMT-B). Assessments were performed at baseline and at the month 3 follow-up visit. Linear mixed models were carried out to evaluate cognitive changes from baseline across all cognitive assessment tests. Result: The current study showed significant (p < 0.05) improvement in cognitive function of patients who were given K-Vie™ compared with placebo across the RAVLT, DSST and TMT-B performance assessments. A larger cohort would be beneficial to further confirm the clinical utility of K-Vie™ and assess its effects in acute phases of TBI.